2020
DOI: 10.1037/spy0000187
|View full text |Cite
|
Sign up to set email alerts
|

Navigating early specialization sport: Parent and athlete goal-directed processes.

Abstract: The purpose of this study was to describe the relational processes that exist between parents and athletes when engaged in an early specialization sport. Using an instrumental case study design, 5 parent-athlete (M athlete age ϭ 11.40 years) dyads in Canadian competitive figure skating represented cases for individual and collective analysis. Contextual action theory and the action-project method were used to identify and describe the naturally occurring projects (i.e., joint actions over time) of parents and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
15
0
2
Order By: Relevance
“…Además, esta es una regla también habitual en otros mini-deportes, aunque no muy extendida (Federación Española de Baloncesto [FEB], 2018;RFEBM, 2005). Según Wall et al (2020), existen diferencias entre niños y adultos con respecto a los factores que promueve la práctica deportiva, porque mientras los entrenadores se centran más en variables externas, los jugadores aluden a motivos intrínsecos.…”
Section: Discussionunclassified
“…Además, esta es una regla también habitual en otros mini-deportes, aunque no muy extendida (Federación Española de Baloncesto [FEB], 2018;RFEBM, 2005). Según Wall et al (2020), existen diferencias entre niños y adultos con respecto a los factores que promueve la práctica deportiva, porque mientras los entrenadores se centran más en variables externas, los jugadores aluden a motivos intrínsecos.…”
Section: Discussionunclassified
“…33 This awareness of growth and development from a parental view has been successful in other sports. 34,65 The complexity of multi-discipline sports training and the multiple pressures of discipline coaches makes the education and support of parents a recommendation moving forwards.…”
Section: Discussionmentioning
confidence: 99%
“…Parental involvement in sport is fundamental to provide developmentally appropriate opportunities and support navigating training and competition across multiple sports; therefore insight into parental management is important to consider. 34 This current paper aims to present the landscape of training in youth athletes aspiring to become pentathletes over a five month period capturing internal (session rating of perceived exertion (sRPE), wellness) and external (time, training frequency, training mode) TL factors for each session completed. 35 Alongside the youth athlete data collection, parental interviews will provide information of how the training weeks are developed and what challenges are associated with training for a multi-discipline sport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cross-case level, the presentation of findings involves organizing the identification of projects, actions, and other content in a way that addresses the guiding research questions and illustrated by quotations from participants. For example, in a study exploring how parents and athletes jointly navigate the transition to competitive figure skating, Wall et al (2020) identified three kinds of joint goal-directed projects of parents and athletes: negotiating commitment, progressing toward skating goals, and maintaining a developmental focus. These researchers described each theme in turn, grounded their description in specific examples from their participants, and explained what each kind of project revealed about parental involvement in the decision to pursue early specialization sports at an elite level.…”
Section: Procedures For Conducting Action-project Methods Studiesmentioning
confidence: 99%